Victim hierarchies in the domestic violence disclosure scheme. Issue 2 (May 2018) - Duggan, Marian
Since its national implementation in March 2014, the UK Domestic Violence Disclosure Scheme (also known as 'Clare's Law') has enabled thousands of people in England and Wales to seek information from the police about whether their partner has a history of domestically abusive behaviours. Politicians have hailed the policy on the basis that it empowers people to make informed choices about their safety, thus representing a vital part of wider domestic violence reduction strategies. This, of course, is all dependent upon people knowing the policy exists; being able to apply to it; meeting the relevant criteria; there being information to disclose; and this being relayed to the applicant accordingly. Drawing on empirical research into the policy's operation in one policing area, this paper highlights several discrepancies with respect to how the scheme is functioning. The analysis suggests that the hierarchical, two-tier approach to implementation is impacting on displaced responsibility and potential risk enhancement, while the symbolic mobilisation of domestic violence victims for contemporary political gain is also explored. The paper concludes with suggestions for reform to boost the ability of the policy to prevent domestic violence and abuse.